Arbitrage Risk and Stock Mispricing - Doukas, John A.; Kim, Chansog (Francis); Pantzalis, Christos (Journal of Financial and Quantitative Analysis, 2010)
Abstract In this paper we examine the relation between equity mispricing and arbitrage risk and find that stocks with high arbitrage risk have higher estimated mispricing than stocks with low arbitrage risk. These results are not limited to high book-to-market or small capitalization stocks, and they are not sensitive to transaction and short-selling costs. In addition, they remain robust to alternative multifactor return generating specification models and mispricing measures. Overall, our empirical results are consistent with the conjecture that mispricing is a manifestation of the inability of arbitrageurs to hedge idiosyncratic risk, a major deterrent to arbitrage activity.